2012
DOI: 10.1007/s00204-012-0823-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of nanosilica particle-induced inflammation by surface modification of the particles

Abstract: It has gradually become evident that nanomaterials, which are widely used in cosmetics, foods, and medicinal products, could induce substantial inflammation. However, the roles played by the physical characteristics of nanomaterials in inflammatory responses have not been elucidated. Here, we examined how particle size and surface modification influenced the inflammatory effects of nanosilica particles, and we investigated the mechanisms by which the particles induced inflammation. We compared the inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 43 publications
2
40
0
2
Order By: Relevance
“…Several reports have demonstrated that the characteristics of NMs, such as surface properties and size, are important factors for the induction of pharmacologic or pharmacokinetic alterations and cellular responses. [12][13][14][15] Three types of nSP70 were used in this experiment: unmodified nSP70, carboxyl group-modified nSP70 (nSP70-C), and amino group-modified nSP70 (nSP-70-N).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have demonstrated that the characteristics of NMs, such as surface properties and size, are important factors for the induction of pharmacologic or pharmacokinetic alterations and cellular responses. [12][13][14][15] Three types of nSP70 were used in this experiment: unmodified nSP70, carboxyl group-modified nSP70 (nSP70-C), and amino group-modified nSP70 (nSP-70-N).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11] In addition, some reports suggest that the size and surface properties of NMs are important for inducing pharmacologic or pharmacokinetic alterations and cellular responses. [12][13][14][15] These suggest that NMs can cause unexpected adverse reactions when they invade the body. Therefore, basic information about the characteristics of NMs and their in vivo and in vitro application is essential for the development of safe NMs.…”
mentioning
confidence: 99%
“…Cytotoxicity profile of silica nanoparticles has received experimental support in different model cell lines, which was considered to be the result of size-/dose-dependent effect and oxidative stress provoked by these particles [13]. Whereas Morishige T. et al [14] did not observe cell death when treated with silica nanoparticles (30-, 50-, 70-nm). On the other hand, a recent study reported that amorphous silica nanoparticles elicited chromosomal aberrations and gene mutations [15].…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios indican que las NP de sílice pueden favorecer respuestas inmunes alérgicas de tipo Th2 en ratones expuestos a OVA, induciendo mayores niveles de inmunoglobulinas IgE, IgG e IgG1 (47). Estas NP también inducen la producción de TNF-a dependiente de la producción de ROS y de la activación de las proteínas cinasas activadas por mitógenos (MAPK, por la sigla en inglés de mitogen-activated protein kinases) en macrófagos, activando una respuesta inflamatoria (48,49). Chen y colaboradores (50) mostraron que cé-lulas de Kupffer estimuladas con NP de sílice liberan grandes cantidades de ROS, TNF-a y óxido nítrico causando inflamación.…”
Section: Nanopartículas De Síliceunclassified
“…Passagne y colaboradores (54) encontraron que las NP de sílice inducen estrés oxidativo, dependiente del tiempo y de su tamaño. Igualmente, se ha demostrado que las NP de sílice no cristalina, de tamaño nano y submicrónico, pueden inducir una alta producción de IL-1β por mecanismos que implican la activación del inflamasoma NLRP3, en macrófagos murinos preactivados con LPS (55) y en macrófagos humanos (48,56,57). Por otro lado, Peeters y colaboradores (58) demostraron que las NP de sílice cristalina inducen la activación del inflamasoma NLRP3 en células humanas derivadas del epitelio bronquial.…”
Section: Nanopartículas De Síliceunclassified